PENGGUNAAN MODEL PEMBELAJARAN INQUIRY PADA MATA PELAJARAN IPS KELAS VI A SDNEGERI 18 TANGAHKOTO SEMESTER II TP 2013/2014 (Universitas PGRI Sumatera Barat, 2015)
This research was conducted by teachers in order to improve the quality of learning in Social Studies learning outcomes that are lower than other subjects. Researchers designed Social Studies using a model of inquiry to determine the effects on student learning outcomes of Social Studies at class VIA of SDN 18, Koto Tangah , Sungaipua district, Agam, West Sumatra. This research aims to show up the effect of inquiry learning model to the results of Social Studies in elementary school student of SDN 18, Koto Tangah , Sungaipua district, Agam, West Sumatra on the basic competence of Understanding the Natural Phenomenon Occurring in Indonesia and its surrounding. The research had the dependent variables related to the learning outcomes of Social Studies and the independent variables related to the inquiry learning model. The research design was Classroom Action Research. Research subjects were 22 students. Data collecting instruments used the form of test results of Social Studies (pre test and posttest). Results of this research are; inquiry learning model has a positive effect on student learning outcomes of Social Studies at class VIA of SDN 18, Koto Tangah , Sungaipua district, Agam, West Sumatra. Inquiry learning model is expected to be disseminated to teachers to be used in accordance with the requirements and can be used as an alternative repertoire of knowledge in the use of learning model that will be applied in the process of learning Social Studies in elementary school. This research is expected to be used as a reference for other teachers for the next research.